A facile preparation route for highly conductive borate cross-linked reduced graphene oxide paper. (24th September 2015) - Tian, Zhengshan; Xu, Chunxiang; Li, Jitao; Zhu, Gangyi; Wu, Jing; Shi, Zengliang; Wang, Yueyue
<x xml:space="preserve">Abstract</x> A simple evolvement process was used to illustrate the fabrication of GO-based paper with excellent conductivity.